2015
DOI: 10.1007/s12671-015-0388-5
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness at Work: Positive Affect, Hope, and Optimism Mediate the Relationship Between Dispositional Mindfulness, Work Engagement, and Well-Being

Abstract: Mindfulness has been described as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
208
2
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(282 citation statements)
references
References 94 publications
26
208
2
22
Order By: Relevance
“…Because mindful individuals are able to observe their experiences without judging, reflecting, evaluating or analyzing those, they become less vulnerable to the negative feelings associated with failure, opinions of others, rewards, status and conflicts (Brown and Ryan, 2003) and develop a capacity to monitor the positive side of life (Wright, 2006). More mindful people report higher levels of positive affect and lower levels of negative affect (Brown and Ryan, 2003) and experience more positive emotions like hope, resilience, and optimism (Malinowski and Lim, 2015;Youssef and Luthans, 2007). The positive and receptive attention to activities leads to an increased perception of detail, information, and subtle social cues, thereby enriching the quality of experiences, making individuals happily immersed in them and more intrinsically motivated (Brown and Ryan, 2003).…”
Section: Mindfulness and Intrinsic Motivationmentioning
confidence: 99%
“…Because mindful individuals are able to observe their experiences without judging, reflecting, evaluating or analyzing those, they become less vulnerable to the negative feelings associated with failure, opinions of others, rewards, status and conflicts (Brown and Ryan, 2003) and develop a capacity to monitor the positive side of life (Wright, 2006). More mindful people report higher levels of positive affect and lower levels of negative affect (Brown and Ryan, 2003) and experience more positive emotions like hope, resilience, and optimism (Malinowski and Lim, 2015;Youssef and Luthans, 2007). The positive and receptive attention to activities leads to an increased perception of detail, information, and subtle social cues, thereby enriching the quality of experiences, making individuals happily immersed in them and more intrinsically motivated (Brown and Ryan, 2003).…”
Section: Mindfulness and Intrinsic Motivationmentioning
confidence: 99%
“…The results of the current study are also in line with previous research showing a positive relationship between positive affect and work engagement (Sonnentag, Mojza, Binnewies, & Scholl, 2008) and help confirm Malinowski and Lim's (2015) findings that positive affect partially mediates the association between mindfulness and work engagement. Malinowski and Lim (2015) drew on Fredrickson's (2001) Broaden and Build theory of positive emotions to propose that by broadening people's thought-action repertoires positive affect would increase personal resources such as hope and optimism, and that those resources would in turn foster greater work engagement.…”
Section: Dispositional Mindfulness and Work Engagementsupporting
confidence: 92%
“…Given the strong association between positive affect and work engagement, mindfulness is 34 expected to enhance engagement via positive affect. That is supported by a recent cross-sectional study of 299 adults in full-time employment that found that positive affect partially mediated the relationship between trait mindfulness and work engagement (Malinowski & Lim, 2015). …”
mentioning
confidence: 65%
See 2 more Smart Citations